MODEL PERUMAHAN DAN PERMUKIMAN DI DAERAH RAWAN BANJIR: STUDI KASUS DI DESA BULUTIGO, LAREN, LAMONGAN - Subaqin, Agus (saintis, 2009)
This research aimed to know about the aspects cause the settlement formed, and the adaptation patterns of the local community. Further it makes description of housing and settlement model on the area. Descriptive research will use to make systematically, factually and accurately of the observation concerning with the facts and population or the area characterized by typology concept. Classification and building type hierarchy is expected able to describe the housing and settlement in troubled area of flood. The result of this research shows that the housing and settlement model in troubled area of flood consists of Javanese building with Kampong and Limasan type and combination between Kampong and Limasan type . Factors that affect such as the shape of building, environment utility and community adaptation process. Besides, there is a close relationship between the settlement and community income. The information about the model of housing and settlement in troubled area of flood is expected can be used as a consideration to manage and improve the housing and settlement in troubled area of flood.